Impact of co-expression of maize 11 and 18 kDa δ-zeins and 27 kDa γ-zein in transgenic soybeans on protein body structure and sulfur amino acid content. (March 2019) - Kim, Won-Seok; Krishnan, Hari B.
Highlights: Transgenic soybean plants expressing different classes of zeins were generated. Zeins accumulated in ER-derived protein bodies and vacuoles. Co-expressing the 18 kDa δ-zein and 27 kDa γ-zein resulted in larger protein bodies. Soybeans co-expressing 18 kDa δ-zein and 27 kDa γ-zein had higher methionine content. Abstract: The methionine-rich seed storage proteins of maize have been expressed in transgenic plants as a means to improve the overall sulfur amino acid content of seed. Previous attempts to increase the sulfur amino acid content of soybean seeds by this approach has met with limited success. It has been shown co-expression of different class of zeins can result in their stable accumulation in transgenic plants. In this study, conventional crosses between transgenic plants individually expressing 11, 18 kDa δ-zeins and 27 kDa γ-zein were made to obtain plants that simultaneously express both the δ-zein and γ-zein. Transmission electron microscopic observation of thin-sections of transgenic soybean seeds revealed that the zeins accumulated in ER-derived protein bodies (PBs) which were found sparsely scattered in cytoplasm. The size of these PBs varied from 0.2 to 0.6 μm in soybean plants individually expressing 11, 18 kDa δ-zeins and 27 kDa γ-zein. In contrast, soybeans co-expressing the 18 kDa δ-zein and 27 kDa γ-zein the PBs was 3–4 times larger. Electron microscopic observation also revealed the sequestration of PBs inside the vacuoles where they could be subjected to degradation by vacuolar proteases. Amino acid analysis of transgenic soybean individually expressing 11, 18 kDa δ-zeins and 27 kDa γ-zein revealed only a minimal increase in the overall methionine content compared to the wild-type. In contrast, plants co-expressing 18 kDa δ-zein and 27 kDa γ-zein showed a significant increase (27%) in the methionine content compared to the control seeds.